Standarisasi Senyawa Diosgenin Pada Tumbuhan : Review Artikel - Vriezka Mierza; Anisa Fauziah; Riani Riani; Sulastri Sulastri; Siti Farikha; Faizal Auladi Rivianto (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Diosgenin is a steroid sapogenin composed of a hydrophilic sugar with a hydrophobic steroid aglycone which functions as a starting material in the production of steroid drugs and hormones. Pharmacologically, diosgenin has been widely used as a treatment for leukemia, inflammation, hypercholesterolemia, and cancer. Diosgenin compounds are contained in plants such as abutilon indicum L, Coctus speciosus, tubers of Dioscorea spp, and fenugreek seeds. In order to guarantee the quality of the product, the active compounds must be standardized, so that uniform raw materials can be obtained and the pharmacological effects of these plants can be guaranteed. This article review was carried out by means of literature studies using secondary data in the form of journals and articles to standardize diosgenin compounds in several plants using high performance liquid chromatography (HPLC), high performance thin layer chromatography (HPTLC), ultra high performance liquid chromatography (UPLC) methods. and thin layer chromatography (TLC).